Charged-particles measurements in low-pressure iodine plasmas used for electric propulsion. (1st August 2022) - Esteves, B; Marmuse, F; Drag, C; Bourdon, A; Laguna, A Alvarez; Chabert, P
Abstract: This paper investigates iodine as an alternative propellant for space plasma propulsion. Measurements are taken in a low-pressure inductively-coupled plasma chamber used as the ionization stage of a gridded ion-engine. Langmuir probes are used to measure the electron density and the electron energy distribution functions spatial variations between the inductive coil and the extraction grids for several radio-frequency (RF) powers and mass flow rates. Measurements in iodine are compared to xenon, krypton and argon in order to evaluate performances of these various propellants for ionization (and therefore power) efficiency. At low mass flow rates, iodine is found to be the most efficient propellant, however, as the mass flow rate increases, the ionization cost in iodine increases rapidly due to both its molecular and electronegative nature. The ratio of negative ion to electron density is measured using laser-induced photodetachment in order to quantify the effect of iodine electronegativity. Finally, all measurements are compared to a previously published global (volume-averaged) model. The agreement between model and experiments is acceptable, however several modelling improvements are proposed.